Idiomatikal pada Stand Up Comedy Kiky Saputri dan Ate roasting Amin - Lestari, Intan; Rani Ardesi Pratiwi; Reza Pahlevi Ginting (Global Action and Education for Society, 2026)
The purpose of this research is (1) to describe the types of idiomatic expressions found in Kiky Saputri's stand-up comedy roasting Amin, and (2) to describe the idiomatic functions found in Kiky Saputri's stand-up comedy roasting Amin. The data in this research consists of idiomatic expressions found in Kiky Saputri's and Ate's roasting of Amin. The data source in this research is a video on YouTube titled